Interspecific interactions between Coptotermes gestroi and Heterotermes tenuis (Isoptera: Rhinotermitidae) under laboratory conditions - Lima, Juliana Toledo [UNESP]; Costa-Leonardo, Ana Maria [UNESP] (My University, 2006)
Coptotermes gestroi and Heterotermes tenuis are termite pests. Both species have cryptic habits, and are known as subterranean termites. The aim of this study was to verify if food availability and alterations in the proportion of soldiers interfere in the interactions between these termites, since the introduced species C. gestroi occupies the same niche as the native species H. tenuis. Different bioassays were conducted in order to evaluate these interspecific interactions. The results showed that C. gestroi presented advantages in the occupation of territory in all bioassays and suggest a higher efficiency of this species in the search for alternative food sources, especially when the number of soldiers was higher than that of H. tenuis. Additionally, it is possible to conclude that food availability and the different proportion of soldiers involved in the interspecific confrontations interfere in the occupation of territory and in the agonistic behavior between these two species of termites.
Keywords: Agonistic behavior; Competition; Coptotermes; Heterotermes; Subterranean termites; Coptotermes gestroi; Heterotermes tenuis; Isoptera; Rhinotermitidae